2021
DOI: 10.1097/ta.0000000000003039
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of prehospital triage tools for identifying major trauma in elderly injured patients: A systematic review

Abstract: This is a repository copy of Diagnostic accuracy of prehospital triage tools for identifying major trauma in elderly injured patients: A systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…2). After obtaining and reviewing full-text articles, 10 studies were excluded as they were not original research (literature review, articles, and editorial) [27][28][29][30], not focused in evaluating prehospital triage [10,[31][32][33], assessed a specific injury mechanism [34], or used the same data of another included study [35]. The quality assessment of the remaining 23 articles was performed independently by two reviewers.…”
Section: Resultsmentioning
confidence: 99%
“…2). After obtaining and reviewing full-text articles, 10 studies were excluded as they were not original research (literature review, articles, and editorial) [27][28][29][30], not focused in evaluating prehospital triage [10,[31][32][33], assessed a specific injury mechanism [34], or used the same data of another included study [35]. The quality assessment of the remaining 23 articles was performed independently by two reviewers.…”
Section: Resultsmentioning
confidence: 99%
“…This is a matter of great interest internationally, and this includes surveillance of literature and implementation of changes if justified. A recent systematic review of elderly-specific triage criteria found no studies that could demonstrate undertriage levels below the 5% recommended by American College of Surgeons Committee on Trauma 17,37 . Third, use of video assisted EMDC triage, recently deployed at most EMDCs in Norway, should be encouraged and assessed according to dispatch precision.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of the CENTER TBI study. The challenge of accurately triaging older patients is well recognised (19)(20)(21)(22)(23)(24)(25), and the poor accuracy of all current methods was the finding of a recent systematic review (26). This may be explained by the different pathophysiology of traumatic brain injury in the two cohorts, highlighted by the greater likelihood of intracranial injury in the low energy cohort yet a higher presenting GCS (Table 3) (18).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%